Vehicle Noise, Vibration, and Sound Quality - Sheng, Gang (SAE International, 2012)
Gives readers a working knowledge of vehicle vibration, noise, and sound quality. The knowledge it imparts can be applied to analyse real-world problems and devise solutions that reduce vibration, control noise, and improve sound quality in all vehicles - ground, aerospace, rail, and marine.